Use and influence of Delivery and Birth Plans in the humanizing delivery process - María Suárez-Cortés; David Armero-Barranco; Manuel Canteras-Jordana; María Emilia Martínez-Roche (Universidade de São Paulo, 2015)
OBJECTIVES: get to know, analyze and describe the current situation of the Delivery and Birth Plans in our context, comparing the delivery and birth process between women who presented a Delivery and Birth Plan and those who did not.METHOD: quantitative and cross-sectional, observational, descriptive and comparative cohort study, carried out over two years. All women who gave birth during the study period were selected, including 9303 women in the study.RESULTS: 132 Delivery and Birth Plans were presented during the first year of study and 108 during the second. Among the variables analyzed, a significant difference was found in "skin to skin contact", "choice of dilation and delivery posture", "use of enema", "intake of foods or fluids", "eutocic deliveries", "late clamping of the umbilical cord" and "perineal shaving".CONCLUSIONS: the Delivery and Birth Plans positively influence the delivery process and its outcome. Health policies are needed to increase the number of Delivery and Birth Plans in our hospitals.